Causes and prognosis of chronic intestinal pseudo-obstruction in 48 subjects: A 10-year retrospective case series. Issue 36 (September 2018) - Lu, Wei; Xiao, Yongtao; Huang, Jianhu; Lu, Lina; Tao, Yiqing; Yan, Weihui; Cao, Yi; Cai, Wei
Abstract : Abstract: The aim of the study was to evaluate the prognosis and survival of pediatric subjects with chronic intestinal pseudo-obstruction (CIPO) and investigate the independent risk factors affecting their prognosis. This was a retrospective case series of all pediatric subjects suffering from CIPO and treated at the Pediatric Surgical ward of Xinhua Hospital between January 2006 and January 2016. The overall mortality was 19/48 (39.6%). Because of delayed CIPO diagnosis, many subjects underwent a variety of surgical procedures. The rate of additional surgical procedures was high (35/48, 72.9%), but the number of surgical procedures, parenteral nutrition, and megacystis did not affect mortality. Mycotic infection was significantly associated with mortality, while onset at <1 year and hypoganglionosis showed a tendency to be associated with mortality. Mycotic infection was associated with mortality of children with CIPO. Despite improving treatment approaches, the overall prognosis of CIPO remains poor. The choice of the surgical intervention could be based on standard criteria.